Edmund Roberts papers - Roberts, Edmund, 1784-1836.; Roberts, Edmund, 1784-1836. in the U.S. sloop-of-war Peacock ... during the years 1832-3-4.
Official and family correspondence, journals, manuscript drafts of Roberts's book Embassy to the Eastern Courts of Cochin-China, Siam, and Muscat; in the U.S. Sloop-of-war Peacock, David Geisinger, Commander, During the Years 1832-3-4 (1837), diplomatic documents (1832-1836), legal and financial records, and miscellaneous items consisting chiefly of maps, drawings, and printed matter. Documents Roberts's service as a special agent of the U.S. to negotiate treaties with Siam, Muscat, and Cochin China; the people, customs, languages, religions, and arts that he encountered in South America and Asia; and his difficulties in obtaining remuneration from Congress for expenses incurred during his voyages. Includes photocopies of an 1835 commission signed by Andrew Jackson to negotiate a treaty with Japan. Correspondents include Mahlon Dickerson, Edward Livingston, Eugene A. Vail, and Levi Woodbury.
Microfilm edition available, in part
Microfilm produced from originals in the Manuscript Division.
Merchant and diplomat.
Collection material in English, with Chinese, Portuguese, and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
A portion of the collection previously cataloged separately under Edmund Roberts commission in the Miscellaneous Manuscript collection.
Keywords: Dickerson, Mahlon, -- 1770-1853 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Livingston, Edward, -- 1764-1836 -- Correspondence; Vail, Eugene A. -- Correspondence; Woodbury, Levi, -- 1789-1851 -- Correspondence; Roberts family -- Correspondence; United States. -- Navy -- Foreign service -- Pacific Area; Peacock (Sloop of war); Arts -- Asia; Arts -- South America; Diplomatic and consular service, American; Asia -- Description and travel; Asia -- Languages; Asia -- Religion; Asia -- Social life and customs; Japan -- Foreign relations -- United States; Muscat (Oman) -- History; Oman -- Foreign relations -- United States; South America -- Description and travel; South America -- Languages; South America -- Religion; South America -- Social life and customs; Thailand -- Foreign relations -- United States; United States -- Foreign relations -- 1829-1847.; United States -- Foreign relations -- Japan; United States -- Foreign relations -- Oman; United States -- Foreign relations -- Thailand; United States -- Foreign relations -- Vietnam; Vietnam -- Foreign relations -- United States; Diplomats; Merchants